Comparative analysis of the small RNA transcriptomes of miiuy croaker revealed microRNA-mediated regulation of TLR signaling pathway response to Vibrio anguillarum infection. (May 2016) - Xu, Guoliang; Han, Jingjing; Xu, Tianjun
Abstract: MicroRNAs (miRNAs) are an abundant class of endogenous noncoding small RNAs (sRNAs) that are partially complementary to their target messenger RNA (mRNA), which post-transcriptionally regulate various biological processes by repressing mRNA translation or inducing mRNA degradation. MiRNAs have been demonstrated to play crucial roles in the host response to infection by diverse pathogens. As an important bacterial pathogen, Vibrio anguillarum has been caused great economic losses in miiuy croaker aquaculture. To identify immune-related miRNAs of miiuy croaker in response to V. anguillarum infection, we constructed two sRNA libraries with or without bacterial infection. High-throughput deep sequencing and subsequent bioinformatic analysis identified 241 conserved and 137 novel miRNA precursors in miiuy croaker based on its whole genome sequences, encoding 293 and 124 mature miRNAs, respectively. Then we compared the expression patterns of miRNAs in the two libraries. There were significant differences in the expression of 12 miRNAs between the infection group (IG) and control group (CG). Further, the expressions of six miRNAs were validated by real-time quantitative PCR. The target gene prediction and function analysis were conducted for the 12 differential miRNAs. This analysis revealed that these miRNAs participated in the regulation multiple immune-related signaling pathways. Transcription factors in TLR signaling, such as AP-1, IRF5, NF-κB and IRF3, were activated by these miRNAs via post-transcriptionally regulating the expression of TLRs and TLR-associated signaling proteins, inducing effective host immune response to eradicate infectious pathogens. This is the first study of the identification and characterization of miiuy croaker miRNAs in response to V. anguillarum infection. The comprehensive analysis of the expression of miRNAs and the target gene and function prediction of differently expressed miRNAs may help to understand the regulatory mechanisms of miRNA in fish during the interaction between host and bacterial pathogens. Highlights: Two sRNA libraries were constructed with or without Vibrio anguillarum infection. A total of 378 miRNA precursors were identified in miiuy croaker. Antisense miRNA transcripts were found to contribute to the origin of novel miRNAs. Differentially expressed miRNAs were identified and validated by qRT-PCR. A negative regulation map of TLR signaling mediated by miRNA was constructed.